Optimising germinated conditions to enhance yield of resveratrol content in peanut sprout using response surface methodology. (21st June 2016) - Miao, Yu; Hong‐zhi, Liu; Ying, Yang; Ai‐min, Shi; Li, Liu; Hui, Hu; Qiang, Wang; Hong‐wei, Yu; Xiao‐he, Wang
Summary: Peanut sprout has associated with enhance the content of a nonflavonoids known as resveratrol, which influences a variety of functions including against cancer, cardiovascular and delaying ageing. Peanut from Liaoning province of China was used as a material to accumulate resveratrol during germination. The individual effects of soaking temperature and time as well as germination temperature, time and humidity on resveratrol accumulation in 5 days germinated peanut were investigated. Then, based on Box–Behnken design, interactive effects of the germination parameters were evaluated by response surface methodology. The optimum conditions were as follows: soaking temperature at 35 °C, soaking time at 8 h, germination temperature at 29 °C, germination humidity at 90%, and germination time at 5 day. Under the optimum condition, resveratrol content reached 32.87 μg g −1, which was almost 9.78 times higher than that in the peanut which did not germinate. Abstract : This paper optimised the condition of accumulating resveratrol during peanut germination. Under the optimum conditions, resveratrol content can reached to 32.87 μg g ‐1, which was almost 9.78 times higher than that in the peanut which not germinated.